CONTEMPORARY CHALLENGES OF ACUTE RESPIRATORY INFECTIONS IN PEDIATRIC ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Acute respiratory infections (ARIs) remain one of the leading causes of morbidity and hospitalization among children globally. The heterogeneity of viral and bacterial pathogens involved, compounded by evolving epidemiological trends post-COVID-19, presents significant diagnostic and therapeutic challenges, especially in low- and middle-income countries (LMICs).